Safety of the applicability of neuromuscular electro-stimulation in hemodynamics of patients in ICU's as a prevention of polyuromyopathy: a literature review (Research, Society and Development, 2022)
Aim: To assert the safety of using neuromuscular electro-stimulation on ICU patients as a way to prevent polyneuromyopathy. Methods: This study comes as a literature revision with researches concentrated on databases such as PubMed, SciELO, Medline and Cochrane from early March until Abril 2020, with no idiom restrictions, and with its main analysis being written between the months of May and June. There have been inserted articles with informations on the safety and effects of the applicability of the technic in the outcomes, taking in consideration possible hemodynamics alterations. Results: There have been identified 234 relevant studies, from which 215 have been excluded for not presenting relevant and safe outcomes, and there were included 5 randomized clinical trials. Sample size has varied between 11 and 54 patients from both genders, in an age range from 18 to 82 years old, involving or not the use of invasive mechanical ventilation, who were submitted to neuromuscular electrical stimulation in critically ill patients. Amongst the selected articles, all of them analyzed the influence from the neuromuscular electrical stimulation and didn't recognize side effects that could influence in the patient's clinical condition. Conclusion: The analysis results suggest that the neuromuscular electro-stimulation (NMES) could be implemented in ICUs for the recovery and prevention of polyneuromyopathy, hence the lack of malefic or relevant side effects.